One step beyond a broad molecular phylogenetic analysis: Species delimitation of Adenomera marmorata Steindachner, 1867 (Anura: Leptodactylidae) - Cassini, Carla S.; Taucce, Pedro P. G. [UNESP]; Carvalho, Thiago R. de [UNESP]; Fouquet, Antoine; Sole, Mirco; Haddad, Celio F. B. [UNESP]; Garcia, Paulo C. A. (Public Library Science, 2020)
Taxonomists always have had intense discussions about how species should be delimited and recently many studies have used integrative approaches by combining molecular, morphological, and bioacoustic data. Although these studies are paramount for understanding species diversity, few of them actually formalize species delimitations to the final step of nomenclatural acts. Historically, the Neotropical frog genus Adenomera has been considered as a difficult taxonomic group because it comprises many morphologically similar species exhibiting high levels of intraspecific polymorphism. A recent work using molecular data shed light on the phylogenetic relationships within the genus and identified several lineages that may correspond to undescribed species but did not delimit species boundaries. In the Atlantic Forest, a clade formed by A. marmorata and two putative species (Adenomera sp. J and Adenomera sp. K) were identified. In this paper, we combine morphological, acoustic, and molecular data in order to evaluate species limits within this Atlantic Forest Adenomera clade. We provide a redescription of A. marmorata and restrict its type locality to the Tijuca Massif, in the Municipality of Rio de Janeiro, Brazil. Our results do not support A. marmorata and the two candidate species as diagnosable distinct species. Therefore A. marmorata corresponds to a species with pronounced morphological and acoustic variation in the genus and a complex phylogeographic structure.